Improving the quality of user service at the Archives Center and Library of Binh Duong University - Nguyen, Thụy Thùy Diệu (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The arrangement of user services is one of the core activities of the library to promote, develop and satisfy the needs and interests of users, and also a measure of the effectiveness of a library’s operation. Over the past years, the Archive and Library Center of Binh Duong University has constantly innovated in serving users, but the results have not been as expected. The article investigates the current situation of user service activities at the Archive and Library Center of Binh Duong University, and proposes specific solutions to improve the effectiveness of this activity, meet the best needs of users and the general development strategy of Binh Duong University in the coming time.